SCHOOL PRINCIPALS’ ATTITUDE TO CHANGES IN THE SYSTEM OF EDUCATION - Mečkauskienė, Ramutė; Želvys, Rimantas (Acta Paedagogica Vilnensia, 2012)
In most publications dedicated to the education change in Lithuania, three main periods in education reform practical implementation are usually defined. Lithuanian society differently accents the education reform as a whole and has a discrepant attitude towards the importance of implementing its changes. Some steps of the reform are estimated positively, while other steps are valued less. In 1996 (Želvys, 1996), 2001 (Želvys, et al., 2001) and 2009, (Mečkauskiene, 2009) surveys were conducted in order to find out the school principals’ attitude towards the educational system changes at the end of each period of the education reform in Lithuania. The results of the surveys allow to compare and evaluate the school principals’ attitude towards these changes and to reveal their attitude dynamics in the period of over ten years. A comparative analysis shows that the majority of respondents go on stating that the present educational system is better as compared to the Soviet system of education, and deny the sidelight view in society that educators are longing for the Soviet education system; they show a highly optimistic level of the attitude towards the future of the Lithuanian education system. On the other hand, there has still remained a defensive wish of the majority of school principals to see a less centralized educational system. Moreover, they still go on stating that changes in the education system are being implemented more and more on the “top-down” principle showing the tendency of centralization in the decision-taking. A high stability is seen in the principals’ wish to have more rights in management authorization and the optimization of the school net. The generalized results of 1996, 2001 and 2009 show the stability of school principals’ attitude towards three stages of the educational reform. There is a shift only concerning separate changes. The steady outlooks are usually influenced by the external factors and the changing attitudes to the internal factors.